Breast milk cellular HIV-specific interferon γ responses are associated with protection from peripartum HIV transmission. - Lohman-Payne, B; Slyker, J; Moore, S; Maleche-Obimbo, E; Wamalwa, D; Richardson, B; Rowland-Jones, S; Mbori-Ngacha, D; Farquhar, C; Overbaugh, J; John-Stewart, G (2012)
OBJECTIVE: Breast milk is a major route of infant HIV infection, yet the majority of breast-fed, HIV-exposed infants escape infection by unknown mechanisms. This study aimed to investigate the role of HIV-specific breast milk cells in preventing infant HIV infection. DESIGN: A prospective study was designed to measure associations between maternal breast milk HIV-specific interferon-γ (IFN-γ) responses and infant HIV-1 detection at 1 month of age. METHODS: In a Kenyan cohort of HIV-infected mothers, blood and breast milk HIV-gag IFN-γ ELISpot responses were measured. Logistic regression was used to measure associations between breast milk IFN-γ responses and infant HIV infection at 1 month of age. RESULTS: IFN-γ responses were detected in breast milk from 117 of 170 (69%) women. IFN-γ responses were associated with breast milk viral load, levels of macrophage inflammatory protein (MIP) 1α, MIP-1β, regulated upon activation, normal T-cell expressed, and secreted and stromal-cell derived factor 1 and subclinical mastitis. Univariate factors associated with infant HIV infection at 1 month postpartum included both detection and breadth of breast milk IFN-γ response (P = 0.08, P = 0.04, respectively), breast milk MIP-1β detection (P = 0.05), and plasma (P = 0.004) and breast milk (P = 0.004) viral load. In multivariate analyses adjusting for breast milk viral load and MIP-1β, breast milk IFN-γ responses were associated with an approximately 70% reduction in infant HIV infection [adjusted odds ratio (aOR) 0.29, 95% confidence interval (CI) 0.092-0.91], and each additional peptide pool targeted was associated with an approximately 35% reduction in infant HIV (aOR 0.65, 95% CI 0.44-0.97). CONCLUSION: These data show breast milk HIV-gag-specific IFN-γ cellular immune responses are prevalent and may contribute to protection from early HIV transmission. More broadly, these data suggest breast milk cellular responses are potentially influential in decreasing mother-to-child transmission of viruses.